2018
DOI: 10.1038/s41586-018-0222-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for extremely rapid magma ocean crystallization and crust formation on Mars

Abstract: The formation of a primordial crust is a critical step in the evolution of terrestrial planets but the timing of this process is poorly understood. The mineral zircon is a powerful tool for constraining crust formation because it can be accurately dated with the uranium-to-lead (U-Pb) isotopic decay system and is resistant to subsequent alteration. Moreover, given the high concentration of hafnium in zircon, the lutetium-to-hafnium (Lu-Hf) isotopic decay system can be used to determine the nature and formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
144
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(155 citation statements)
references
References 43 publications
11
144
0
Order By: Relevance
“…Therefore comparison of physical and chemical properties of Mars with those of the Earth can provide important insights into the origin and evolution of the rocky planets, especially conditions for a habitable planet formation. Radioisotope dating of Martian meteorites demonstrates that its accretion and evolution occurred earlier than that of the Earth (Dauphas and Pourmand, 2011;Kruijer et al, 2017b;Bouvier et al, 2018). The rapid formation of Mars is consistent with a pebble accretion and/or runaway and oligarchic growth model, depending upon model assumptions (Dauphas and Pourmand, 2011;Johansen et al, 2015;Levison et al, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…Therefore comparison of physical and chemical properties of Mars with those of the Earth can provide important insights into the origin and evolution of the rocky planets, especially conditions for a habitable planet formation. Radioisotope dating of Martian meteorites demonstrates that its accretion and evolution occurred earlier than that of the Earth (Dauphas and Pourmand, 2011;Kruijer et al, 2017b;Bouvier et al, 2018). The rapid formation of Mars is consistent with a pebble accretion and/or runaway and oligarchic growth model, depending upon model assumptions (Dauphas and Pourmand, 2011;Johansen et al, 2015;Levison et al, 2015).…”
Section: Introductionmentioning
confidence: 78%
“…; Bouvier et al. ), and the mantle appears to have formed a series of isotopically distinct reservoirs from which subsequent magmas were derived with little mixing (Debaille et al. ).…”
Section: Objective 3: Quantitatively Determine the Evolutionary Timelmentioning
confidence: 99%
“…From the analysis of the ratio of lead isotopes, 207 Pb/ 206 Pb, in zircon crystals contained in the material of the Martian meteorite NWA 7034, Bouvier et al (2018) concluded that the core formation and the crystallization of a magma ocean on Mars was completed in less than 20 Myr after the formation of the Solar System. These results agree with those reported by Mezger et al (2013) concerning the studies of the decay of a system of short-lived isotopes 182 Hf-182 W, which point to an age not larger than 10 Myr after the formation of the Solar System.…”
Section: Ipatovmentioning
confidence: 99%